Rationalized Haar Series for Approach Homogeneous and Non-Homogeneous State Equations - Al-Jourany, Khalid Hadi Hameed (Arab Journal for Sciences and Research Publishing, 2022)
In this paper, we give a new approximate solution method to homogeneous and non-homogeneous state equations using rationalized Haar functions. Integration operational matrix of rationalized Haar functions are used to convert the computation of homogeneous and non homogeneous state equations to a simple system of algebraic equations. By using the method (based on Matlab programming) on numerical analysis examples, we show that our method has high degree of accuracy.